Effect of Illumination on Ocular Status Modifications Induced by Short-Term 3D TV Viewing - Yuanyuan Chen; Yuwen Wang; Xinping Yu; Aiqin Xu; Jian Jiang; Hao Chen (Neural Plasticity)
Objectives. This study aimed to compare changes in ocular status after 3D TV viewing under three modes of illumination and thereby identify optimal illumination for 3D TV viewing. Methods. The following measures of ocular status were assessed: the accommodative response, accommodative microfluctuation, accommodative facility, relative accommodation, gradient accommodative convergence/accommodation (AC/A) ratio, phoria, and fusional vergence. The observers watched 3D television for 90 minutes through 3D shutter glasses under three illumination modes: A, complete darkness; B, back illumination (50 lx); and C, front illumination (130 lx). The ocular status of the observers was assessed both before and after the viewing. Results. After 3D TV viewing, the accommodative response and accommodative microfluctuation were significantly changed under illumination Modes A and B. The near positive fusional vergence decreased significantly after the 90-minute 3D viewing session under each illumination mode, and this effect was not significantly different among the three modes. Conclusions. Short-term 3D viewing modified the ocular status of adults. The least amount of such change occurred with front illumination, suggesting that this type of illumination is an appropriate mode for 3D shutter TV viewing.